Penerapan Model Pembelajaran pada Hasil Belajar Matematika berdasarkan Asal Sekolah dan Jenis Kelamin Siswa - Al Ayyubi, Ibnu Imam; Martini, Sofia; Fitriyah, Dzul; Yasmin, Sabrina; Azizah, Azzah (Journal of Primary Education Research, 2024)
This research aims to see the differences and interactions that occur in students' mathematics learning outcomes based on the application of learning models that are reviewed based on the student's gender. This research used a quantitative research approach carried out at SDN Pasirbanteng, MI Ar-Ridhwan, MIS Pasirpogor I, MI Sukarasa, and SDN Saapan with a sample of 41 students at SDN Pasirbanteng, 33 students at MI Ar-Ridhwan, 20 students at MIS Pasirpogor I, 24 students at MI Sukarasa, and 30 students at SDN Saapan with a total of 148 students in class IV. The learning models applied at SDN Pasirbanteng, MI Ar-Ridhwan, MIS Pasirpogor I, MI Sukarasa, and SDN Saapan are Contextual, Cooperative, Project Based Learning (PjBL), Problem-Based Learning (PBL), and Inquiry. The method in this research uses the survey method and the Analysis of Variance test. This research instrument uses a test to test the data analysis requirements used, consisting of a normality test using Kolmogorov-Smirnov and Shapiro-Wilk with the help of SPSS version 26 software. However, if the data normality assumption is not met, a Non-Parametric Test, namely the Median Test, is carried out. In this research, it was found that there were differences between the learning models used in mathematics learning, but this did not occur when viewed based on the gender of the students. An interaction between the learning model and student gender was also not found. The contextual learning model with PjBL, PBL, Inquiry and the cooperative learning model with PjBL, PBL, and Inquiry each have significant differences. However, there is no difference between contextual and cooperative learning models, PjBL and PBL, PjBL with inquiry, and PBL with inquiry.